If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2h = 20 Solving 5 + 2h = 20 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2h = 20 + -5 Combine like terms: 5 + -5 = 0 0 + 2h = 20 + -5 2h = 20 + -5 Combine like terms: 20 + -5 = 15 2h = 15 Divide each side by '2'. h = 7.5 Simplifying h = 7.5
| -72-3(-9-4)=3(-9-4)+6 | | 5y-5=10 | | 8x-3(x-4)=3(x-4)+6 | | 2y-7=9 | | y=4x+3whatisy | | 3x-2(2+5)=2(x+3)-8 | | 10x+14=34 | | -5x+5=10 | | y=3+4x | | -10x+6=26 | | -x+4y=3 | | 5v-20=25 | | 3x+4=5x+4 | | 1.5x=x+1.5 | | 3y^3-6xy+2x^3=-1.26 | | 6x+84=3x-12 | | (3d-4)/6+1=(d+1)/8 | | 5x-4+2*x=8*x-3x+15-16 | | 0.08x+0.09(9000-x)=750 | | 7+6x=2x-5 | | 4x-3=5x+5 | | 37=0.1x+7 | | 5x+10=2x+40 | | 3(x+4)=4(x+1) | | 3x^2-5x-4(x^2-3x)=6 | | -2x=100+18e | | x^2+y^2-4x+12y=9 | | 3(x+16)=4x+5 | | m^2-6m=15 | | 8x-60=-30 | | (8)-(4)= | | 2(2x-3)+2x=45 |